2020
DOI: 10.3846/jbem.2020.13569
|View full text |Cite
|
Sign up to set email alerts
|

Capital Market Development and Economic Growth: An Ardl Approach for Saudi Arabia, 1985–2018

Abstract: The aim of this paper is to analyze and test the effects of capital market development on the per-capita GDP growth in Saudi Arabian economy covering the period of 1985-2018. An ARDL, FMOLS and Johansen tests are implemented. The stock market indicators: share price index, capitalization, liquidity, number of share transactions, and number of shares are employed using a log-linear eclectic model designed to fit the availability of data. Capitalization and liquidity came up with negative signs, contrary to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…The third most common theme among capital market research articles is Capital market development with 6 articles among the selected publications. The findings from these groups revealed that some capital market variables had positive signs as expected (Algaeed, 2020); the Capital or Stock market is positively related and positively impacts economic growth (Ibrahim & Mohammed, 2020;Angaye & Frank, 2020). In fourth place among the themes is Capital market performance having 5 selected articles for the systematic review.…”
Section: Article Typementioning
confidence: 72%
“…The third most common theme among capital market research articles is Capital market development with 6 articles among the selected publications. The findings from these groups revealed that some capital market variables had positive signs as expected (Algaeed, 2020); the Capital or Stock market is positively related and positively impacts economic growth (Ibrahim & Mohammed, 2020;Angaye & Frank, 2020). In fourth place among the themes is Capital market performance having 5 selected articles for the systematic review.…”
Section: Article Typementioning
confidence: 72%
“…Hence, Alam and Hussein (2019) in their paper found that stock market has positive effect on economic growth. Following the paper of Algaeed (2020), in this paper, the indicators representing the stock market are share price index and market capitalization. Similarly, Brasoveanu et al (2008) in their paper confirmed the positive impact of capital market development on economic growth.…”
Section: Interrelationship Between Capital Markets and Economic Growthmentioning
confidence: 99%
“…The process of raising finance is related to issuing securities such as bills, promissory notes, shares, bonds etc. Capital markets are especially important for the riskier businesses, because they cannot obtain funds from the banking sector (Algaeed, 2020). The capital markets, which are structured in stock and commodities markets, serve as a synonym for the liquidity and the performance of the economy.…”
Section: Interrelationship Between Capital Markets and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially when changes in monetary policy affect the strategic choices of firms, firms with aggressive strategies have a greater need for a continuous supply of funds for their R&D and market development activities (Bates et al, 2009). The main role of capital markets is to raise funds through different institutions, where securities financing is an effective way to obtain long-term funding for listed companies, a process that cannot be done without institutional investors (Algaeed, 2021). Secondly: in terms of the reactions of various stakeholders in the capital market, Bentley et al (2013) argue that the auditor, as an external independent third-party service provider, the degree of aggressiveness of the firm's strategy is positively related to the firm's financial irregularities.…”
Section: From the Perspective Of The External Investor Market Stakeholders Have Information Asymmetry In The Interpretation Of Corporate mentioning
confidence: 99%